A comparative study of romantic naturalism in Shafiee Kadkani and Badi Saqour - Hasan goudarzi lamraski, Parinaz Bagheri, Gholamreza pirouz, Ali Akbar Bagheri Khalili (Opción, 2019)
The research aims to criticize the differences and similarities observed in the works of Shafiee Kadkani and Badi Saqouron. The methodology of this paper is a content analysis that is carried out through comparison of two selected Persian and Arabic collections. As a result, the morning and spring in nature are similar in both works and they are taken to refer to hope. As a conclusion, the comparison of the works of well-known and foreign poets creates a new perspective on the culture and art of other countries and also one's own country in addition to recognizing the new works.